Evaluation of the nutritional quality of French children breakfasts according to the Breakfast Quality Score (BQS) - Poinsot, Romane; Hopkins, Sinead; Maillot, Matthieu (Frontiers in Nutrition, 2024)
Background : Breakfast meals provide essential nutrients and energy to children and adolescents. Based on recommendations from the International Breakfast Research Initiative (IBRI), the Breakfast Quality Score (BQS) was developed to assess breakfast nutritional value among the French adult population. However, its application to children remains unexplored. Objective : This study aimed to evaluate the BQS in assessing the nutritional quality of breakfasts consumed by French children aged 4-17 years. Methods : A total of 4,015 breakfasts, obtained from dietary recalls provided by 1,448 children participating in the French representative dietary survey (INCA3), were analyzed. As for adults, the performance of the BQS was tested through correlations with other nutritional indicators and comparison of nutrients and dietary components between tertiles of scores. The study examined the regularity of breakfast consumption and compared the BQS of children's breakfasts across socio-demographic modalities and breakfast categories distinguished by their primary grain component. Additionally, a predictive modeling using Partial Least Squares (PLS) regression identified influential INCA3 food groups. Results : The majority of children consumed solid breakfasts regularly. Socio-professional category, household income and food insecurity influenced BQS, revealing contradictory disparities. Ready-to-eat cereal (RTEC) breakfasts had the highest BQS (73.5% for children and 73.1% for adolescent), while biscuits and viennoiseries scored the lowest (52.% for children and 49.1% for adolescent). PLS highlighted RTECs, milk, and hot beverages (mainly containing chocolate milk) as being positively associated with BQS, while sweet beverages and viennoiseries were negatively associated. Conclusion : The study demonstrates the effectiveness of the BQS in assessing children's breakfast quality, with RTEC breakfasts showing the highest nutritional value. The findings provide insights into factors influencing breakfast nutritional quality and underscore the importance of promoting healthier breakfast choices among all children.